Influence of die-back syndrome on reproductive strategies within Phragmites australis populations. (4th March 2019) - Cerri, Martina; Ferranti, Francesco; Coppi, Andrea; Foggi, Bruno; Gigante, Daniela; Lastrucci, Lorenzo; Onofri, Andrea; Venanzoni, Roberto; Viciani, Daniele; Reale, Lara
Abstract: Sexual plant reproduction is a strategy that allows plant populations to increase genetic variability, and consequently to be more efficient in adapting to new environments and to overcome stress conditions. Here, we focus on the reproductive mode of Phragmites australis, an important sub-cosmopolite species that can spread both by clonal propagation and sexual reproduction. In Europe, P. australis is affected by severe decline (known as Reed Die-Back Syndrome or RDBS); this study aims to understand if in RDBS condition the reproductive strategy of P. australis was altered, based on the hypothesis that if stress occurs, plants are likely to use their energy to increase genetic variability to overcome the stress. Inflorescences in five Italian wetlands were sampled from healthy and RDBS-affected stands of P. australis. Seed production, seed viability and seed germination were evaluated, with germination monitored under two different water conditions: moist and submerged. Stress induced by RDBS appears to influence the reproductive strategy of P. australis. In RDBS-affected stands, seed production was significantly higher than healthy stands for four of five sites. Seed viability and germination were also higher in RDBS-affected stands, but these differences were lower and site dependent.